To kill a mockingbird - Lee, Harper (New York : Grand Central Pub., 2010)
Eight-year-old "Scout" Finch tells of life in a small Alabama town where her father is a lawyer.
Notable/Best Books (A.L.A.).
Wilson's Fiction.
Wilson's Senior High School.
Book Links (A.L.A.), April 2001.
Booklist, June 2006.
Library Journal, March 1995.
Keywords: Fathers and daughters -- Southern States -- Fiction; Girls -- Southern States -- Fiction; Lawyers -- Southern States -- Fiction; Trials (Rape) -- Southern States -- Fiction; Bildungsromans; Domestic fiction; Father-daughter relationship -- Fiction; Girls -- Fiction; Legal stories; Trials (Rape) -- Fiction; Southern States -- Race relations -- Fiction; Southern States -- Race relations -- Fiction; Bildungsromans; Domestic fiction; Legal stories